Pengaruh Ekstrak Etanol Nanas (Ananas Comocus) Terhadap Kadar Kolesterol Total dan Trigliserida Pada Tikus Wistar Putih (Rattus Novergicus) Hiperkolesterolamia Melalui Review Jurnal Periode 2010 - 2020 : none - NOER KUMALA INDAHSARI; PRIMA WIBISONO (Universitas Hang Tuah, 2023)
Hypercholesterolemia is a condition in which cholesterol levels in the body are not normal / dyslipidemia, this happens because of today's instantaneous lifestyle. Hypercholesterolemia can affect anyone (age or gender), but it can be treated with one way, namely eating high-fiber foods obtained from fruits, vegetables, nuts and others. One source of vegetable fiber is pineapple (Ananas Comosus), which contains many vitamins and fiber, from leaves to tubers. Niacin is one of the ingredients of pineapple which can lower cholesterol levels in the blood. The purpose of this study was to determine the The method used was a Systematic Review. The results of the journal review showed that pineapple extract can reduce total cholesterol and triglyceride levels in white wistar rats which are hypercholesterolemic using the pineapple extract method at a dose of 100 mg / kgBB rats as much as 42.02% then if the dose is increased, the total cholesterol level and triglycerides will decrease even close to the normal rat cholesterol level.